Intracranial residual lesions following early intensification in a patient with T-cell acute lymphoblastic leukemia: a case report - Yuichi Nagamatsu; Takeshi Isoda; Motoki Inaji; Jun Oyama; Daiki Niizato; Dan Tomomasa; Noriko Mitsuiki; Motoi Yamashita; Takahiro Kamiya; Kohsuke Imai; Hirokazu Kanegane; Tomohiro Morio; et al. (BMC, 2024)
Abstract Background T-cell acute lymphoblastic leukemia (T-ALL) tends to involve central nervous system (CNS) infiltration at diagnosis. However, cases of residual CNS lesions detected at the end of induction and post early intensification have not been recorded in patients with T-ALL. Also, the ratio and prognosis of patients with residual intracranial lesions have not been defined. Case presentation A 9-year-old boy with T-ALL had multiple intracranial tumors, which were still detected post early intensification. To investigate residual CNS lesions, we used 11C-methionine (MET)-positron emission tomography. Negative MET uptake in CNS lesions and excellent MRD status in bone marrow allowed continuing therapies without hematopoietic cell transplantation. Conclusions In cases with residual lesions on imaging studies, treatment strategies should be considered by the systemic response, direct assessment of spinal fluid, along with further development of noninvasive imaging methods in CNS. Further retrospective or prospective studies are required to determine the prognosis and frequency of cases with residual intracranial lesions after induction therapy.